PENGARUH BUDAYA, SOSIAL, PERSONAL, DAN PSIKOLOGIS TERHADAP PERILAKU MEMILIH KEUANGAN SYARIAH DI PROVINSI NANGGROE ACEH DARUSSALAM - Kiki Hardiansyah Siregar; Dini Vientiany; Erliyanti Erliyanti (Fakultas Ekonomi Universitas Negeri Medan, 2023)
The purpose of this study is to determine and analyze how the behavior of the people of Aceh Province in choosing sharia financing as a place to finance motorbikes. This study also aims to find out the obstacles and efforts made by Islamic finance companies so that the people of Aceh choose Islamic finance as a place of financing. This type of research is a quantitative-qualitative method. The analysis technique used in quantitative research is the Structural Equation Model using AMOS 22.1 software, while qualitative research data is obtained through observation, interviews and documentation. The data analysis technique used in this study is an interactive model analysis consisting of data collection, data reduction, data presentation and drawing conclusions. This research resulted in cultural variables with a P value (0.703), social variables with a P value (0.070) and psychological variables with a P value (0.395). Each of these variables does not affect the behavior of the people of Aceh Province in choosing Islamic finance as a place of financing. While personal variables have a positive and significant effect on the P value (0.003) which is below the critical value of 0.05. Meanwhile, cultural, social, personal and psychological variables simultaneously do not influence people's behavior in choosing Islamic finance. The variables of culture on personal, cultural on psychology and social on psychology have a positive and significant effect, where each P value is brought to a critical value of 0.05. Personal variables and psychological variables do not have an indirect influence on the behavior of the people of Aceh Province in choosing Islamic finance with culture as an intervening variable. Likewise, personal and psychological variables do not have an indirect influence on the behavior of the people of Aceh Province in choosing Islamic finance with social as an intervening variable.